Development of a Sensitive and Specific Polyclonal Antibody for Serological Detection of Clavibacter michiganensis subsp. sepedonicus - Przewodowski, Włodzimierz (PLoS One, 2017)
The quarantine bacterium Clavibacter michiganensis subsp. sepedonicus (Cms) causes bacterial ring rot (BRR) in potato but is difficult to detect, hampering the diagnosis of this disease. ELISA immunoassays have not been widely used to detect Cms because commercially available anti-Cms antibodies detect mainly EPS-producing bacteria and can fail to detect strains that do not produce EPS. In the current study, we developed a new type of polyclonal antibody that specifically detects Clavibacter michiganensis subsp. sepedonicus bacteria irrespective of their EPS level. We first found that the presence of bacterial EPS precluded quantitative measurement of bacteria by currently available immunoenzymatic methods, but that washing Cms cells with acidic and basic buffers to remove EPS before analysis successfully standardized ELISA results. We used a mix of three strains of Cms with diverse EPS levels to generate antigen for production of antibodies recognizing Cms cells with and without an EPS layer (IgG-EPS and IgG-N-EPS, respectively). The resulting IgG-N-EPS recognized almost all Cms strains tested in this work regardless of their mucoidal level. The availability of this new antibody renders immunological diagnostics of Cms more sensitive and reliable, as our newly developed antibodies can be used in many type of immunoassays. This work represents an important step forward in efforts to diagnose and prevent the spread of BRR, and the methods and solutions developed in this work are covered by six Polish, one European and one US patents.